"Pillaring Effects" in Cross-Linked Cellulose Biopolymers: A Study of Structure and Properties. (23rd August 2018) - Udoetok, Inimfon A.; Wilson, Lee D.; Headley, John V.
Abstract : Modified cellulose materials (CLE-4, CLE-1, and CLE-0.5) were prepared by cross-linking with epichlorohydrin (EP), where the products display variable structure, morphology, and thermal stability. Adsorptive probes such as nitrogen gas and phenolic dyes in aqueous solution reveal that cross-linked cellulose has greater accessible surface area (SA) than native cellulose. The results also reveal that the SA of cross-linked cellulose increased with greater EP content, except for CLE-0.5. The attenuation of SA for CLE-0.5 may relate to surface grafting onto cellulose beyond the stoichiometric cellulose and EP ratio since ca. 30% of the hydroxyl groups of cellulose are accessible for cross-linking reaction due to its tertiary fibril nature. Scanning electron microscopy (SEM) results reveal the variable surface roughness and fibre domains of cellulose due to cross-linking. X-ray diffraction (XRD) and 13 C NMR spectroscopy indicate that cellulose adopts a one-chain triclinic unit cell structure (P1 space group) with gauche-trans ( gt ) and trans - gauche ( tg ) conformations of the glucosyl linkages and hydroxymethyl groups. The structural characterization results reveal that cross-linking of cellulose occurs at the amorphous domains. By contrast, the crystalline domains are preserved according to similar features in the XRD, FTIR, and 13 C NMR spectra of cellulose and its cross-linked forms. This study contributes to an improved understanding of the role of cross-linking of native cellulose in its structure and functional properties. Cross-linked cellulose has variable surface functionality, structure, and textural properties that contribute significantly to their unique physicochemical properties over its native form.